Algerian legal framework for the elimination of international double taxation: Insights from the Algeria–UK tax convention - Henni, Mohamed Fouad; Ayad, Saadi (The International tax journal, 2025)
This study aims to attain a critical and essential objective to clarify and understanding the role of international tax treaties in the international taxation practices. This will be achieved by examining the various provisions and mechanisms that are designed to eliminate or reduce double taxation, with a focus on the Algerian-UK treaty as a case study. The study found that international tax treaties play a crucial role in preventing double taxation by establishing clear rules for allocating taxing rights between countries. The Algeria-United Kingdom tax treaty, in particular, applies key principles such as tax sovereignty, reciprocity, and non-discrimination to ensure fair taxation. It effectively addresses various types of income and profits through mechanisms like tax credits, exemptions, and allocation rules, reducing the tax burden on cross-border economic activities.